Объяснение:
y=(x³-5x²-6x)/x
1) Функция определена, если x ≠ 0 , т.к делить на нуль нельзя, тогда функция примет вид:
y = x*(x²-5x-6)/x ;
y = x*(x²-5x-6)
y = x²-5x-6 ; x ≠ 0
xв = -b/2a = 5/2 = 2,5
yв = (5/2)² - 5 * 5/2 - 6 = 25/4 - 25/2 - 6 = (25-50-24)/4 = -49/4 = - 12,25
А ( 2,5 ; -12,25 ) - вершина
Объяснение:
y=(x³-5x²-6x)/x
1) Функция определена, если x ≠ 0 , т.к делить на нуль нельзя, тогда функция примет вид:
y = x*(x²-5x-6)/x ;
y = x*(x²-5x-6)
y = x²-5x-6 ; x ≠ 0
xв = -b/2a = 5/2 = 2,5
yв = (5/2)² - 5 * 5/2 - 6 = 25/4 - 25/2 - 6 = (25-50-24)/4 = -49/4 = - 12,25
А ( 2,5 ; -12,25 ) - вершина
y=(x³-5x²-6x)/x
1) Функция определена, если x ≠ 0 , т.к делить на нуль нельзя, тогда функция примет вид:
y = x*(x²-5x-6)/x ;
y = x*(x²-5x-6)
y = x²-5x-6 ; x ≠ 0
xв = -b/2a = 5/2 = 2,5
yв = (5/2)² - 5 * 5/2 - 6 = 25/4 - 25/2 - 6 = (25-50-24)/4 = -49/4 = - 12,25
А ( 2,5 ; -12,25 ) - вершина
Объяснение: